The three snow bears - Brett, Jan, 1949- (New York : Putnam, 2007)
The Goldilocks story takes a fine twist when an endearing snow bear family and a curious Inuit girl meet center stage.
Kirkus Review
Library Media Connection
2.8
K-3.
K-3
Keywords: Folklore; Polar bears -- Folklore; Bears -- Folklore; Folklore; Polar bears -- Folklore; Bears -- Folklore; Folklore; Polar bears -- Folklore